Wideband and compact rat‐race coupler for fifth‐generation N77/N78/N79 applications. Issue 10 (14th May 2020) - Zhou, Bo; Zhang, Ziyang; Li, Changkun; Qian, Li; Wang, Yunheng
Abstract: A wideband and compact rat‐race coupler that covers 3 to 5 GHz is proposed for the fifth‐generation new radio N77/N78/N79 applications. The wideband characteristic is obtained by using cascaded two‐section topology and broadside‐coupled lines at each input/output port. Miniaturization of two‐section rings is achieved using meander microstrip lines. A fractional bandwidth of 50% and a size reduction of 60% are both reached. Good in‐phase and out‐of‐phase characteristics are obtained as well. The circuit can be easily fabricated using conventional printed circuit board process and suitable for mass production.